Radical Behaviorism and Eliminative Materialism: a criticism to mentalism (Brazilian Journal of Behavioral and Cognitive Therapy, 2014)
The relations between Radical Behaviorism and Eliminative Materialism are investigated. Despite its peculiarities, these two programs have in common the systematic criticism to the mentalists explanations of folk psychology, claiming a new conceptual structure built in a rigorous scientific context. This aspect justifies the rejection of both to the reductionist project of the Identity Theory, and as this is the most essential criteria of Eliminative Materialism allows it to ignore the exclusive commitment with neurosciences as a substitute of folk psychology, opening space for a radical behaviorist based behavior science to be included in the eliminative project
Keywords: Radical Behaviorism; Eliminativism; Materialism; Folk psychology